Mary and Joseph : A story of faith - Till, Eric (Warner Home Video, 2003)
They were subjects in an occupied land people who probably experienced to live simple, unremembered lives instead they became central players in the world's greatest events. Starring Blanche Baker (Emmy Award Winner for Holocaust) and Jeff East (Superman. The Movie) and filmed on location in Israel, Mary and Joseph: A Story of Faith is an engaging devout and fresh look at the beloved religious figures. The Bible reveals little about them. But using what is known about the social and political issues of that era, an involving yet speculative story can be told in it, the bethrothed pair confront the iron rule of the Roman Empire, the condemnation of religious leaders, the revolutionary fervor of the Zealots and more. In a time when many desired a Messiah who would wield a sword, Mary and Joseph relied on the weapon of faith --and prepared for the Messiah who entered the world as a child.